Imperfect Facsimiles: The Library and the Museum1. Issue 3 (6th September 2021) - Wong, Winnie
Abstract: What can the institutional practices of libraries and museums tell us about the ways in which our culture conceives of knowledge and aesthetics? How might their architectures, and our navigation of them, map upon the distinctions we make in our minds, dividing real from fake, legitimate from illegitimate, art from fact? This article lays out the conceptual and spatial constructs that are the Library and the Museum, detailing how even trivial norms within them uphold crucial philosophical distinctions, for example, surrounding authorship and authenticity. It then examines two recent cases of forgery in order to reveal how and why thinking across the thresholds of these distinctions, tenuous as they are, can provoke moral and legal consequences.